Implementasi Prinsip Akuntabilitas Dalam Keuangan Islam perspektif Al-Quran dan Hadis - Akhmad Sanusi; Muhammad Sauqi; Siliwangi; Akhmad Hariadi; Ahmad Hariadi, Akhmad sanusi (Al-Hasyimi - Jurnal Ilmu Hadis, 2025)
This study explores the critical role of accountability in Islamic finance, particularly how it is applied in key Islamic financial institutions such as Islamic banks, zakat and waqf organizations, Baitul Maal wat Tamwil (BMT), and Islamic cooperatives. In the context of Islamic finance, accountability goes beyond just administrative requirements it embodies a deep moral responsibility to uphold the trust that the community places in these institutions. Drawing from the teachings of the Qur'an and Hadith, this study highlights the values of honesty, transparency, and fairness as fundamental in managing financial transactions and funds in line with Islamic principles. The paper delves into various dimensions of leadership responsibility and the prohibition against misusing funds, emphasizing how these principles are practiced in institutions that operate under Shariah law. It stresses that financial management within Shariah-compliant institutions must be rooted in values like openness, equity, and collaboration, ensuring that the funds are used in a way that benefits the entire Muslim community. Additionally, the study highlights the importance of accountability in fostering trust between the public and Islamic financial institutions, which ultimately contributes to the broader economic empowerment of the ummah. In conclusion, this paper emphasizes that the principle of accountability in Islamic finance is not only a regulatory obligation but a cornerstone in creating a just, transparent, and sustainable economic system. Its implementation ensures that the financial system benefits the Muslim community fairly and equitably.